2013
DOI: 10.3389/fneng.2013.00011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a self-paced hitting task in freely moving rats based on adaptive spike detection from multi-unit M1 cortical signals

Abstract: Invasive brain–computer interfaces (BCIs) may prove to be a useful rehabilitation tool for severely disabled patients. Although some systems have shown to work well in restricted laboratory settings, their usefulness must be tested in less controlled environments. Our objective was to investigate if a specific motor task could reliably be detected from multi-unit intra-cortical signals from freely moving animals. Four rats were trained to hit a retractable paddle (defined as a “hit”). Intra-cortical signals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…The core behavior criterion of IGA is loss of control of Internet use and is represented as persistence in Internet gaming use despite awareness that it is directly harmful to psychosocial functioning (Hammad et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…The core behavior criterion of IGA is loss of control of Internet use and is represented as persistence in Internet gaming use despite awareness that it is directly harmful to psychosocial functioning (Hammad et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, it is important to remove as much noise as possible. In earlier work performed by our group, we found that if wavelet filtering first performed denoising, the movement or event detection accuracy was enhanced .…”
Section: Introductionmentioning
confidence: 71%
“…We refer to our previous work for a detailed description of the behavioral training and implant procedures, and only a summary of the procedures is presented here. Standard psychophysical behavioral techniques were used to train the rats to depress a retractable paddle three consecutive times (to avoid random events) with their preferred forepaw in return for a food reward.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent BCI publications on rats have shown studies of a similar binary task (push a lever to obtain a reward) but using corticospinal tract activity (38) or with detection from multi-unit intra cortical signals (23). The Hammad team (23), using a 4 3 4 intracortical tungsten micro-wire electrode array, found a good detection of the motor task with an accuracy of 75 6 6% when wavelet denoising was applied (n 5 4, t 5 4 weeks), thus illustrating the feasibility of a brain computer interface for generation of command signals in paralyzed individuals.…”
Section: Experimental Design For Ecog Recordingmentioning
confidence: 99%